The Influence of the Current Ratio and Debt to Equity Ratio on Return of Assets Against ANTM Company. Tbk - Purnamawati, Hilda; Noorwasylatusyfa , Erdyani; Sukiman, Iyan (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2024)
This study aims to determine how much influence the current ratio and debt to equity ratio have on the return on assets of the ANTM company. Tbk. This study uses financial report data over a period of 5 years from 2017-2021 as a research sample using SPSS25. The method used in this research is asociative descriptive analysis with a quantitative approach. The instrument used in this research is financial report data for a span of 5 years for each variable. Based on the results of data analysis obtained multiple linear regression equations from the results of hypothesis testing obtained that the results showed that the variable current ratio (X1) and debt to equity ratio (X2) had a calculated F value of 102.762 and a sig value of 0.000 with an F table value of 18.153. With the results of F count > F table and sig count < 0.005, it can be concluded that simultaneously the current ratio and debt to equity ratio affect the return on assets (Y). In this study, it was also found that the coefficient of determination had an effect of 67.9%, which means that the influence of the current ratio and Debt to equity ratio on the return on assets is 67.9%, the remaining 32.1% is influenced by other factors not included in this study